Multinational enterprises in domestic value chains - Cadestin, Charles (OECD Publishing, 2019)
Multinational Enterprises (MNEs) play an important role in host countries' domestic value chains as part of the global activities of these companies in GVCs. MNE affiliates create directly large volumes of output, value added, international trade and jobs, and in addition they generate also important indirect effects. Foreign affiliates in host countries are not only sourcing locally produced inputs, tradeable as well as non-tradeable, but also produce final and intermediate products sold and used within the domestic economy. Based on the OECD Analytical AMNE database, this paper analyses the domestic linkages of MNE affiliates in host economies in order to get better insights in the role MNEs play across countries
Keywords: Science and Technology